Mengamalkan Ilmu: Integrasi Pengetahuan dan Akhlak dalam Perspektif Islam - H, Hartinawanti; Yahya, Muhammad; Ilyas, Abustani (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Knowledge occupies a central position in Islam and serves as a fundamental foundation for the formation of morally upright individuals and civilized societies. However, knowledge is not meant to remain at the level of theoretical understanding; it must be practiced and reflected in daily behavior. This article examines the concept of practicing knowledge from an Islamic perspective, emphasizing the integration of knowledge and moral conduct. Using a library-based research method, this study analyzes relevant verses of the Qur’an, prophetic traditions (hadith), and scholarly perspectives concerning knowledge and its application. The analysis reveals that beneficial knowledge is characterized by its ability to inspire positive behavioral change, cultivate noble character, and contribute to both personal development and social well-being. Knowledge that is not practiced loses its ethical value and fails to achieve its intended purpose. Therefore, the practice of knowledge is a key indicator of meaningful education and plays a crucial role in fostering a moral, responsible, and civilized society.